Reproducibility of measurements and variability of the classification algorithm of Stratus OCT in normal, hypertensive, and glaucomatous patients - Alfonso Antón (Dove Medical Press, 2009)
Alfonso Antón1,2,3, Marta Castany1,2, Marta Pazos-Lopez1,2, Ruben Cuadrado3, Ana Flores3, Miguel Castilla11Hospital de la Esperanza-Hospital del Mar (IMAS), Barcelona, Spain; 2Institut Català de la Retina (ICR), Barcelona, Spain. Glaucoma Department; 3Instituto Universitario de Oftalmobiología Aplicada (IOBA), Universidad de Valladolid, Valladolid, EspañaPurpose: To assess the reproducibility of retinal nerve fiber layer (RNFL) measurements and the variability of the probabilistic classification algorithm in normal, hypertensive and glaucomatous eyes using Stratus optical coherence tomography (OCT).Methods: Forty-nine eyes (13 normal, 17 ocular hypertensive [OHT] and 19 glaucomatous) of 49 subjects were included in this study. RNFL was determined with Stratus OCT using the standard protocol RNFL thickness 3.4. Three different images of each eye were taken consecutively during the same session. To evaluate OCT reproducibility, coefficient of variation (COV) and intraclass correlation coefficient (ICC) were calculated for average thickness (AvgT), superior average thickness (Savg), and inferior average thickness (Iavg) parameters. The variability of the results of the probabilistic classification algorithm, based on the OCT normative database, was also analyzed. The percentage of eyes with changes in the category assigned was calculated for each group.Results: The 50th percentile of COV was 2.96%, 4.00%, and 4.31% for AvgT, Savg, and Iavg, respectively. Glaucoma group presented the largest COV for all three parameters (3.87%, 5.55%, 7.82%). ICC were greater than 0.75 for almost all measures (except from the inferior thickness parameter in the normal group; ICC = 0.64, 95% CI 0.334–0.857). Regarding the probabilistic classification algorithm for the three parameters (AvgT, Savg, Iavg), the percentage of eyes without color-code category changes among the three images was as follows: normal group, 100%, 84.6% and 92%; OHT group, 89.5%, 52.7%, 79%; and Glaucoma group, 82%, 70.6%, and 76.5%, respectively. A probabilistic category switch from pathologic to normal or vice versa was observed in three eyes (15.8%) of the glaucomatous group for the Savg parameter and in two eyes of the OHT group: one eye (5,9%) for the AvgT and one eye (5.9%) for the Savg parameter.Conclusions: OCT RNFL measurements showed a good reproducibility in normal, OHT, and glaucoma eyes. The probabilistic classification for the three main parameters showed certain variability, especially in glaucoma group and OHT group. Therefore, one isolated category result should be interpreted with caution before clinical classification of the patient.Keywords: optical coherence tomography, glaucoma, nerve fiber layer, algorithm classification, reproducibility